(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
Researching the marketing and sales activities of enterprises is, in its essence, an activity related to the full satisfaction of the demands and needs of the subjects in macro and microeconomics, and is now widely used in developed countries. In the article, the importance of choosing the way of sale, their role in the activity of enterprises is described in detail.